Effect of short-circuit in stator windings on the operation of doubly-fed induction generators operating in a wind power system - Diboune, Y.; Hachelaf, R.; Kouchih, D. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Wind energy has been a clean and renewable source of electricity in recent decades, making a significant addition to overall generation, and wind power is one of the most popular sources of renewable energy. Problem. Accurate modeling of wind turbine generators is critical to improve the efficiency of power systems. Doubly-fed induction generator (DFIG) stands out for its economic advantages associated with the use of frequency converters and induction machines. Increasing operating and maintenance costs of wind turbines highlight the need for early fault identification to optimize costs and ensure reliable operation. The goal of this work is to develop a simplified yet effective model for analyzing stator winding short-circuits in DFIGs operating in wind turbines. The model uses line-to-line voltages as inputs and explicitly considers the neutral-point voltage variation under fault conditions. Methodology. The problem was solved using spectral analysis, the model was implemented for 4 kW DFIG wind turbine in MATLAB to validate its effectiveness. Results. The simulation results confirm the effectiveness of the proposed approach for timely fault detection and analysis. It demonstrates computational simplicity by accurately capturing the main fault characteristics, which is preferable to traditional methods such as symmetrical components and FEM. The scientific novelty of the work lies in a methodology for modeling DFIG during stator short-circuits, integrating the effect of elevated neutral voltage during faults using line-to-line voltages in the base model. It also takes into account phenomena such as magnetic saturation, gap effects, and skin effects. The simplicity of the model makes it suitable for condition monitoring and validation of fault-tolerant control algorithms, which distinguishes it from more complex methods such as symmetrical components or the FEM. Practical value. The proposed model offers a pragmatic and reliable approach for monitoring and analyzing defects in DFIG wind turbines. Its versatility and efficiency improve the optimization of maintenance costs and reliability of renewable energy systems.

Вітроенергетика є екологічно чистим та відновлюваним джерелом електроенергії в останні десятиліття, роблячи значний внесок у загальну генерацію енергії, і є одним із найпопулярніших джерел відновлюваної енергії. Проблема. Точне моделювання вітрогенераторів є критично важливим для підвищення ефективності енергосистем. Асинхронний генератор з подвійним живленням (DFIG) відрізняється економічними перевагами, пов’язаними з використанням перетворювачів частоти та асинхронних машин. Зростання витрат на експлуатацію та технічне обслуговування вітрогенераторів призводить до необхідності раннього виявлення несправностей для оптимізації витрат та забезпечення надійної роботи. Метою даної роботи є розробка спрощеної, але ефективної моделі для розрахунку короткого замикання обмотки статора DFIG, що працює у вітрогенераторі. Модель використовує значення лінійної напруги та враховує підвищення напруги в нейтральній точці у разі несправностей. Методика. Завдання вирішено за допомогою спектрального аналізу. Модель реалізована у MATLAB для вітрогенератора DFIG потужністю 4 кВт для підтвердження її ефективності. Результати моделювання підтверджують ефективність запропонованого підходу до своєчасного виявлення та аналізу несправностей. Модель демонструє обчислювальну простоту, точно фіксуючи основні характеристики несправностей, що краще традиційних методів, таких як симетричні компоненти та метод скінченних елементів (МСЕ). Наукова новизна роботи полягає в методології моделювання DFIG при коротких замиканнях статора, що враховує вплив підвищеної напруги нейтралі при коротких замиканнях з використанням лінійних напруг базової моделі. Модель також враховує такі явища, як магнітне насичення, вплив зазору та скін-ефект. Простота моделі робить її придатною для моніторингу стану та валідації алгоритмів стійкості до відмови, що відрізняє її від складніших методів, таких як симетричні компоненти або МСЕ. Практична значимість. Розроблена модель пропонує практичний та надійний підхід до моніторингу та аналізу дефектів у вітрових турбінах з DFIG. Її універсальність та ефективність сприяють оптимізації витрат на технічне обслуговування та підвищенню надійності систем відновлюваної енергетики.
Keywords: asynchronous generator; short-circuit fault; wind turbine; асинхронний генератор; коротке замикання; вітрова турбіна